Effect of Interactive Invention and Traditional Lecture Instruction on Pre-Service Teachers’ Interest in Cell Biology - Edidiong Emmanuel Akpan; Alice Morenike Olagunju (Scientia Publica Media, 2026)
Cell biology is an important concept in biology that helps students understand other concepts in the field. Students’ interest has continued to wane over the years as a result of poor performance in the cell biology course. Therefore, this study sought to determine the impact of interactive invention and traditional instruction on student teachers’ interest in cell biology. The study also aimed to investigate the effect of problem-solving ability on pre-service teachers’ interest in cell biology as a moderator. Three (3) hypotheses were formulated to guide the study. A pretest-posttest control group quasi-experimental research design was employed. Four hundred and four pre-service teachers participated in the study. The study utilised all available NCE 1 pre-service biology teachers in the biology education programme in the Colleges of Education (CoEs). An instructional guide for interactive invention and conventional lecture instruction, along with a pre-service interest questionnaire (r = 0.82) and a pre-service problem-solving ability test (r = 0.79), were used to collect data. All instruments were validated, and their reliability was established. Data were analysed using Analysis of Covariance (ANCOVA), Estimated Marginal Means (EMM), and graphical illustrations. Findings indicate that pre-service teachers in interactive instruction had a higher post-interest mean score compared to their counterparts in traditional lecture instruction. There was no significant effect of problem-solving ability on pre-service teachers’ interest. The two-way interaction effect of treatment and problem-solving ability was also not significant. Based on these findings, lecturers are encouraged to utilise interactive instruction when teaching cell biology at the College of Education.